Comparison of Postoperative Outcomes of Ureteroscopic Lithotripsy with and without Double J Stent in Patients with Upper Ureteric Stone (Journal of Fatima Jinnah Medical University, 2025)
Background: Ureteroscopic lithotripsy with stent placement is a standard treatment for upper ureteric stones. However, the necessity of routine double J (DJ) stenting is debated due to potential postoperative discomfort. This study aimed to compare postoperative urinary symptoms and stone clearance in patients with and without DJ stent placement.Patients and Methods: A randomized controlled trial was conducted in the Urology Department of Fatima Jinnah Medical University, Sir Ganga Ram Hospital, Lahore, from January 2022 to February 2023. Sixty patients aged 18–45 years with a solitary upper ureteral stone (10–15 mm) confirmed on non-contrast CT scan were included. Patients were randomized into two equal groups: Group A (DJ stent) underwent ureteroscopy with intracorporeal lithotripsy and DJ stent placement; Group B (No stent) underwent the same procedure without stent insertion. Postoperative outcomes included urinary frequency (>8 voids/24h), urgency, dysuria, and stone clearance (≤3 mm residual stone on X-ray KUB at two weeks). Data were analyzed using SPSS v25.0; chi-square test was applied with a significance level of p≤0.05.Results: The mean age was 30.68±8.08 years, with 56.7% males and 43.3% females. Mean stone size was 13.03±1.66 mm. Right-sided stones were seen in 45% and left-sided in 55%. Group A reported significantly more urinary frequency (56.7% vs. 23.3%; p=0.008) and urgency (53.0% vs. 20.0%; p=0.007). Dysuria was also higher in Group A (33.3% vs. 16.7%; p=0.136). Stone clearance was 100% in both groups.Conclusion: Routine DJ stent placement after ureteroscopic lithotripsy results in significantly higher urinary frequency and urgency and relatively increased dysuria, with no difference in stone clearance.
Keywords: Ureteric stone; Ureteroscopic Lithotripsy; Double J; Routine, Stent; Outcome